The influence of operating parameters on the performance and emissions of a DI diesel engine using methanol-blended-diesel fuel - SAYIN, CENK (ELSEVIER SCI LTD, 2010)
In this study, the effects of injection pressure and timing on the performance and emission characteristics of a DI diesel engine using methanol (5%, 10% and 15%) blended-diesel fuel were investigated. The tests were conducted on three different injection pressures (180, 200 and 220 bar) and timings (15 degrees, 20 degrees, and 25 degrees CA BTDC) at 20 Nm engine load and 2200 rpm. The results indicated that brake specific fuel consumption (BSFC), brake specific energy consumption (BSEC), and nitrogen oxides (NOx) emissions increased as brake thermal efficiency (BTE), smoke opacity, carbon monoxide (CO) and total unburned hydrocarbon (THC) decreased with increasing amount of methanol in the fuel mixture. The best results were achieved for BSFC, BSEC and BTE at the original injection pressure and timing. For the all test fuels, the increasing injection pressure and timing caused to decrease in the smoke opacity, CO, THC emissions while NOx emissions increase. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alternative fuel; Methanol; Diesel engine; Injection pressure; Injection timing; EXHAUST EMISSIONS; COMBUSTION CHARACTERISTICS; SOOT; BIODIESEL; SMOKE; OIL